10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BackgroundImmune checkpoint inhibitors have reshaped the treatment of recurrent or metastatic head and neck squamous cell carcinoma (HNSCC) and are increasingly used in perioperative settings. Unlike conventional therapy, immunotherapy may produce atypical response patterns, including delayed response, mixed or dissociated response, pseudoprogression, and hyperprogression.ObjectiveTo summarize current evidence on immunotherapy-related pseudoprogression in HNSCC and propose a practical risk-adapted framework for clinical management.MethodsThis structured narrative review searched PubMed, Web of Science, Embase, Google Scholar, and relevant gray literature from database inception to March 2026. HNSCC-specific studies were prioritized. Evidence from other solid tumors was included only when relevant to general mechanisms, imaging criteria, circulating tumor DNA dynamics, or immune-related response patterns.ResultsPseudoprogression appears uncommon in HNSCC, but its clinical impact is disproportionate because small changes in tumor volume or inflammation may threaten the airway, swallowing tract, tracheostomy site, skin envelope, or carotid artery. Proposed mechanisms include immune-cell infiltration, inflammatory edema, tumor necrosis, increased vascular permeability, and hemorrhage. Low-risk, clinically stable patients may undergo continued immunotherapy with short-interval reassessment. In contrast, laryngeal, hypopharyngeal, tracheostomal, carotid-adjacent, skull-base, cervical esophageal, or rapidly symptomatic disease should be managed as true progression or impending local failure until proven otherwise.ConclusionsPseudoprogression in HNSCC should not be treated as a purely radiologic event. We propose an HNSCC-modified iRECIST approach in which observation is reserved for patients with clinical stability, low-risk anatomy, and feasible short-interval reassessment.